PERFORMANCE ANALYZING OF AN ORGANIC RANKINE CYCLE UNDER DIFFERENT AMBIENT CONDITIONS - Akkaya, A. V. (YILDIZ TECHNICAL UNIV, 2017)
The goal of this study is to develop a thermodynamic model in order to show the effect of ambient conditions on performance of an Organic Rankine Cycle based power generation system. This system is simply consisted of a turbine, a condenser, a boiler, pumps and a cooling tower. Each component in this system is modeled based on energy and mass balance equations. Then, the system model is obtained with integration of component models. After that, simulation studies are iteratively carried out to determine the performance of the considered system under variation of ambient conditions such as dry bulb temperature and relative humidity. Simulation results show that that Organic Rankine Cycle performance can be sensitive to the seasonal and daily variation of the ambient conditions.
Keywords: Organic Rankine cycle; Cooling tower; Ambient Conditions; Performance; WASTE HEAT-RECOVERY; WORKING FLUIDS; TEMPERATURE; ORC; SYSTEM; GAS; Thermodynamics